Comparison of chemical and physical decontamination of alginate dental impression material (Research, Society and Development, 2024)
The decontamination of dental impression materials is essential to prevent cross-infections, and therefore different protocols and disinfection methods have been studied. The aim of this in vitro study was to evaluate the efficacy of ultraviolet light (UV-C) in microbial reduction of dental impression material (alginate – irreversible hydrocolloid). Circular alginate specimens were contaminated with a suspension of 10⁷ CFU/mL of Staphylococcus aureus and subjected to UV-C radiation (UV SURFACE, BioLambda, São Paulo, Brazil, λ = 254 nm) with different irradiation times, in addition to 1% sodium hypochlorite. The samples were divided into 4 groups: G1 - Control (n=3), G2 - 1% Sodium Hypochlorite for 10 min (n=3), G3 - UV-C radiation for 5 s (n=3), G4 - UV-C radiation for 10 s (n=3). Microbial samples were collected before and after decontamination methods, and the number of colony-forming units (CFU/mL) was determined. The data were statistically analyzed using ANOVA and Tukey tests (p